PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA SLIDESGO KELAS V SDN 13 BATU GADANG KOTA PADANG - Aulia, Delima; Hamimah Hamimah; Arwin Arwin; Yanti Fitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of students in IPAS (Science and Social Studies) learning in grade V of SDN 13 Batu Gadang, Padang City. The purpose of this study was to improve students’ learning outcomes through the implementation of the Problem Based Learning (PBL) model assisted by Slidesgo media. This research employed Classroom Action Research (CAR) consisting of two cycles, each including planning, implementation, observation, and reflection stages. The subjects of this study were 25 fifth-grade students. Data were collected through observation, tests, and documentation, then analyzed using qualitative and quantitative descriptive techniques. The results showed a significant improvement in each cycle. The learning planning increased from 91.67% in Cycle I to 95.83% in Cycle II. The implementation of learning also improved, with teacher and student activities reaching 96.43% categorized as very good. Furthermore, students’ learning outcomes increased from an average score of 75.28 in Cycle I to 85.32 in Cycle II. Therefore, it can be concluded that the application of the Problem Based Learning model assisted by Slidesgo media effectively improves students’ learning outcomes in IPAS learning. Keywords: Problem Based Learning, Slidesgo , learning outcomes , IPAS